Psychosocial Impact of False-Positive Newborn Screening Results: A Scoping Review - Jane Chudleigh; Pru Holder (MDPI AG, 2024)
Psychosocial consequences of false-positive results following newborn bloodspot screening have been identified as a potential risk to this highly successful public health initiative. A scoping review was undertaken in October 2023 underpinned by the Arksey and O'Malley framework. Twenty-four papers were included in the review, many of which focused on cystic fibrosis. The results indicated that impact of false-positive results is variable; some studies suggest false-positive results have the potential to result in negative sequelae including increased stress and changes in parental perceptions of their child, while others suggest these impacts are transient and, in some instances, may even lead to positive outcomes. Further evidence is needed to ensure the representation of other conditions included in newborn bloodspot screening and to support strategies to overcome potential negative sequela.